Correlation between cleft width and dental arch symmetry in cleft lip and palate: a longitudinal study - Eloá Cristina Passucci AMBROSIO; Maria Giulia Rezende PUCCIARELLI; Chiarella SFORZA; Simone SOARES; Márcio de MENEZES; Cleide Felício Carvalho CARRARA; Maria Aparecida Andrade Moreira MACHADO; Thais Marchini OLIVEIRA (Sociedade Brasileira de Pesquisa Odontológica, 2023)
Abstract This study aimed to evaluate the influence of cleft width on dental arch symmetry of children with unilateral cleft lip and palate. Forty-one children were subjected to impression preoperatively (T1; mean age = 0.31 ± 0.07 years) and postoperatively (T2; mean age = 6 .73 ± 1.02 years). Eighty-two digitized dental casts were analyzed by stereophotogrammetry software. The cleft palate width was measured in the anterior (P-P'), middle (M-M'), and posterior (U-U') regions. Also, the following measurements were obtained: anterior intersegment (I-C') and intrasegment (I-C); total intersegment (I-T') and intrasegment (I-T); cleft-side (C'-T') and non-cleft-side (C-T) canine tuberosity. Paired t test and Pearson correlation coefficient were applied (α = 5%). Cleft width had the following means: 10.16 (± 3.46) mm for P-P', 12.45 (± 3.00) mm for M-M', and 12.57 (± 2.71) mm for U-U'. In the longitudinal analysis, I-C' had a significant reduction, while the other measurements significantly increased (p < 0.001). Asymmetry was verified in the following analyses at T1: I-C' vs. I-C and I-T' vs. I-T (p < 0.001); at T2, only in I-C' vs. I-C (p < 0.001). At T1, P-P' vs. I-C' (r = 0.722 and p < 0.001), P-P' vs. I-T' (r = 0.593 and p < 0.001), M-M' vs. I-C' (r = 0.620 and p < 0.001), and M-M' vs. I-T' (r = 0.327 and p < 0.05) showed a positive and significant correlation. At T2, there was a correlation between M-M' and I-C' (r = 0.377 and p < 0.05). In conclusion, the anterior and middle cleft widths influenced palatal asymmetry in the first months of life, while middle width influenced residual asymmetry.